Five Methods of Quran Memorization in Tahfidz House of Fastabiqul Khairat Indonesia - Engkizar, Engkizar; Sarianti, Yulia; Namira, Silva; Budiman, Setria; Susanti, Hendra; Albizar, Albizar (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2022)
Degradation of morals or moral decadence has attacked young generations, especially college students. Therefore, this paper aims to find out forms of moral decadence found in college students. This research uses a qualitative method with a case study approach, the data were collected through direct interviews with ten informants (college students) by using the purposive sampling technique. To strengthen interview data, the writer performed passive participation observation by coming directly to the observed location. All results of the interview were analyzed using Milles and Hauberman’s pattern. The research found nine forms of moral decadence in college students. They are: i) negligent in worship, ii)sexual promiscuity, iii) involved in drug abuse, iv) hedonism, v) revealing awrah, vi) lack of ethics, vii) impolite speaking, viii) dishonest in academics and ix) lack of time management. The results of this research can be used as initial data for future research investigating similar problems in different contexts and issues.